Subtle violence and jealousy in a relationship between students in a public university in Lima East - Cynthia Peña Tasayco (2019)
Objective: determine the significant relationship between subtle violence and jealousy in a couplerelationship in students of a public university in East Lima. The non-experimental crosssectionaldesign with correlational scope was used. Likewise, an intentional non-probabilistic samplingwas conducted, conformed 242 young people of both sexes with ages between 18 and 27 years.Theinstruments used for data collection were the Covert Violence Scale (EVE) of (Lascorz, 2015) and theInventory Multidimensional of Jealousy (Diaz-Loving et al., 1989). Results: They showed that there isa highly significant association between subtle violence and jealousy (P <0.001). In which he found that75.6% of the participants stated that they had used subtle violence with their partners at some time intheir lives; In the same way, 66.1% of students are prone to demonstrate inappropriate behaviors whenperceiving or misinterpreting their partner’s interaction with their peers. Conclusions: It was found thatthere is a highly significant association between subtle violence and jealousy, demonstrating that bothvariables are related to each other within a couple relationship.